PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID PADA MATERI ORGAN PERNAPASAN PADA MANUSIA SISWA KELAS V SDN MOJOROTO 2 - Della Yulia Ningtyas; Kharisma Eka Putri; Alfi Laila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the IPAS learning process, students are taught about living things, inanimate objects in the universe, and their interactions. A learning model that is not accompanied by appropriate media may fail to stimulate students’ interest and enthusiasm, thereby hindering the effectiveness of learning evaluation due to student boredom and lack of motivation. Developing instructional media using Android-Based Interactive Multimedia is the solution offered by the researcher based on a needs analysis. This study aims to determine the validity, practicality, and effectiveness of Android-Based Interactive Multimedia. The research method used is R&D (Research and Development) with the ADDIE development model. The subjects of this study consisted of 28 students and 1 homeroom teacher. Data collection techniques included validity (questionnaires from media and material experts), practicality (questionnaires from teacher and student responses), and effectiveness (post-test). The validity data from the media expert showed a score of 86%, and the validation results from the material expert showed a score of 91%, both categorized as very valid. The practicality data based on teacher responses showed a score of 84%, and student responses showed a score of 91%, both categorized as very practical. The effectiveness data based on classical student mastery showed a score of 94%, categorized as very effective. Based on these results, it can be concluded that the Android-Based Interactive Multimedia on the topic of human respiratory organs is considered to be very valid, very practical, and very effective for use in teaching the topic of human respiratory organs.Bagian Atas Formulir